Peningkatan Keterampilan Menceritakan Isi Dongeng dengan Menggunakan Metode Bermain Peran pada Siswa Kelas III SD Negeri Kintelan 1 Yogyakarta Tahun Ajaran 2016/2017 - Galang Purwanto (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract:The classroom action research is aimed to describe the improvement skill in storytelling the contents of fairy tale through role play method to the third grade students of SD Negeri Kintelan 1 Yogyakarta. This type of research is Classroom Action Research (CAR). The subjects of this study are students of grade 3, amounting to the 29 students. The object of this research are the whole process and the application of the role play method which is used to improve the storytelling skill of the third grade students of SD Negeri Kintelan 1 Yogyakarta. The Data collection techniques that be used are observation, tests and documentation. The test of the instrument uses an expert judgment trial. The results show the average value of storytelling skills on pre-action 68.10. In the first cycle increased by 5.79% to 72.04. In the second cycle increased by 6.38% to 76.64. The number of students who have reached KKM on pre action are 14 students or 48.27%. In the first cycle increased to 16 students or 55.17% of students. In the second cycle increased to 25 students or 86.20% of the 29 students who have reached the KKM. These results indicate that the role play method can improve the skill in storytelling the contents of fairy tale at the third grade students of SD Negeri Kintelan 1 Yogyakarta in the academic year 2016/2017.